LCâMS/MS assay for the determination of natamycin in rabbit and human plasma: Application to a pharmacokinetics and protein binding study - Yashpal Singh Chhonker; Devendra Kumar; Pankaj Shrivastava; Deepak Kumar; Rajbir Singh; Hardik Chandasana; Rabi Sankar Bhatta (Elsevier, 2013)
To enable reliable quantification of natamycin in rabbit and human plasma, a validated, sensitive and selective liquid chromatographyâtandem mass spectrometry assay was developed. The chromatographic separation was achieved isocratically on a Cyano column using methanol: aqueous 3.5Â mM ammonium acetate (pH 4) (90:10Â v/v). The assay was validated over a concentration range of 6.25â400Â ng/mL with lower limit of detection of 3.12Â ng/mL. Quantification was performed using the transitions 664.5â137.2m/z for natamycin and 923.5â183.4m/z for the IS. The method was validated with respect to linearity, accuracy, precision, recovery and stability. This assay has been successfully applied to a pharmacokinetic study of natamycin in NZ rabbit and plasma protein binding in human plasma. Keywords: Natamycin, LCâMS/MS, Pharmacokinetics, Protein binding